Organic Trace Minerals at Lower Concentrations Can Replace Inorganic TraceMineral Premix in Broiler Chicken Diet - Rama Rao, S. V.; Raju, M. V. L. N.; Nagalakshmi, D.; Savaram, Anusha; Pavan, S. Sai; Prakash, B.; Srilatha, T.; Paul, S. S.; Kannan, A. (Indian Journal of Animal Nutrition, 2025)
An experiment was conducted to study the performance, immune responses, and bone mineral variables in broiler chickens fed organic trace minerals (oTM) at suboptimal concentrations in the diet. A total of 2080 day-old broiler male chicks were randomly distributed into floor pens (6.25 × 4 feet) at the rate of 26 birds per pen. Maize-soybean meal-based control diet was supplemented with inorganic trace mineral premix (iTM; Fe 100, Zn 100, Mn 100, Cu 20, Se 0.50, I 2.5/mg/kg). The iTM premix was replaced in the test diets with oTM to provide minerals at graded levels in the diet (10, 17.5, and 25% of the control diet). Each diet was fed ad libitum to a total of 20 replicates of chicks from 1 to 42 days of age. The body weight gain (BWG) was not affected by supplementing oTM at 20% during 1-14 and 1-28 d of age. Both BWG and feed conversion ratio (FCR) were significantly reduced with an increase in oTM >35%. Both the production variables in groups fed oTM at 20% were similar to those fed the iTM. The relative weight of breast meat was lower (p